Timing of First Antenatal Care (ANC) and Inequalities in Early Initiation of ANC in Nepal - Paudel, Yuba Raj; Jha, Trishna; Mehata, Suresh (Frontiers in Public Health, 2017)
Background The provision and uptake of quality and timely antenatal care (ANC) is an essential element of efforts to improve health outcomes for women and newborn babies. Antenatal consultations assist in early identification and treatment of complications during pregnancy. This study aimed to provide an information on distribution and inequalities in early initiation of ANC in Nepal. Methods The distribution and inequalities in the early initiation of ANC were examined using Nepal Demographic and Health Surveys 2011. Bivariate and multivariate logistic regression was used to assess inequalities. Findings Overall, 70% of the women had started their first ANC at 4 month or earlier. Among participants who had never attended school, just more than half (52%) received first ANC at 4 months or earlier, while majority of participants (97%) who had received higher education received first ANC at recommended time. Similarly, 89% of those from richest quintile and 48% of those from poorest quintile received first ANC at recommended time. In adjusted analysis, women from richest wealth quintile were significantly more likely to initiate ANC early (AOR: 3.74, 95% CI: 2.31–6.05) compared to the poorest. Similarly, women with higher level education were significantly more likely (AOR: 11.40, 95% CI: 5.05–25.73) to initiate ANC early compared to women who had never attended school. A significantly lower odds of early ANC take up was observed among madhesi other caste (AOR: 0.56, 95% CI: 0.35–0.90) compared to brahmin/chhetri women. Women whose pregnancy was unwanted were significantly less likely to attend first ANC at 4 months or early (AOR: 0.73, 95% CI: 0.58–0.93) in comparison to women whose pregnancy was wanted. Conclusion The differences in the recommended timing of initiation of ANC were evident among women with different educational, economic levels, and caste/ethnic groups. Rural women were less likely to have checkups as per guidelines. The findings suggest to a need of interventions to raise female education and improve economic status of households. Targeted interventions suitable to local context and culture are equally important. Increasing access to family planning methods and reduction of unwanted pregnancy can promote early ANC take up.